Illuminae - Kaufman, Amie; Kristoff, Jay (Kaufman, Amie. Illuminae files, 2015)
"The planet Kerenza is attacked, and Kady and Ezra find themselves on a space fleet fleeing the enemy, while their ship's artificial intelligence system and a deadly plague may be the end of them all"--